Pemanfaatan limbah perkebunan (kayu karet) menggunakan tungku beehives modifikasi - Bahfie, F.; Nurjaman, F.; Herlina, U.; Shofi, A.; Sumardi, S. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2021)
Biomass can be used for energy production from renewable sources. Due to the social resistance to crop burning, mixtures and pellets made from or including waste materials are a good alternative. Plantation waste becomes a problem, namely reducing land which ultimately destroys the soil and the ecosystem around the land. This waste has the potential to become charcoal that supports biomass production in Indonesia with modified beehive furnaces. The carbonized rubber charcoal has a fixed carbon content of 63% with 37% of ash, volatile and water impurities. And the redemption value in this process is around 15% which has a profit margin of 200% from the purchase capital of rubber wood waste. The carbonization process with modified beehive furnaces can be a recommendation for the manufacture of charcoal from plantation waste.